PENGARUH GAYA KEPEMIMPINAN DAN IKLIM KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus Pada KSPPS Tunas Artha Mandiri Cabang Tasikmalaya) - Fernando Aldiansyah; Cece Rakhmat; Rita Tri Yusnita (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to determine the influence of leadership style and work climate on employee performance at KSPPS Tunas Artha Mandiri Tasikmalaya Branch employees (Case Study on KSPPS Tunas Artha Mandiri Tasikmalaya Branch). The method used is a quantitative approach with a research sample of 36 respondents from employees of KSPPS Tunas Artha Mandiri Tasikmalaya Branch. The data used are primary data and secondary data. The analytical tool used in this study is multiple linear regression analysis using SPSS version 25. The results show that simultaneously leadership style and work climate have a significant effect on employee performance. Partially leadership style has a significant effect on employee performance. Partially the work climate has a significant effect on employee performance.